1988
DOI: 10.1111/j.1754-4505.1988.tb00726.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental treatment needs among hospitalized adult mental patients

Abstract: This survey determines the dental care needs of hospitalized adults with psychiatric and mental disorders. Comprehensive clinical and radiographic oral examinations, conducted on 33% of the patients in a large state mental hospital, found that extensive unmet needs existed in this population. The major requirements were for prophylaxis, calculus removal, and periodontal therapy. The patients' needs varied depending on several demographic factors, including length of hospitalization and psychiatric diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 5 publications
6
37
0
5
Order By: Relevance
“…About 92 % patients of this study group required some kind of gingival / periodontal treatment which was similar to the findings of Barnes and Hede [2,12], while the control group exhibited lower prevalence with 83.49% patients requiring intervention.…”
supporting
confidence: 87%
“…About 92 % patients of this study group required some kind of gingival / periodontal treatment which was similar to the findings of Barnes and Hede [2,12], while the control group exhibited lower prevalence with 83.49% patients requiring intervention.…”
supporting
confidence: 87%
“…Several studies of the oral health of psychiatric patients in different countries have showed that mental illnesses and the psychotropic medications used to treat them can increase the prevalence and the severity of dental diseases (e.g., caries) [520]. Schizophrenia should be considered a risk factor for poor oral health because patients with schizophrenia are likely to face a unique set of factors that lead to the development of advanced oral diseases—and to receive less oral health care [2128].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies of the dental health of these patients have shown that they have extensive dental needs, which has a negative impact on their quality of life [5, 6, 12, 20, 25, 27]. Long-term hospitalisation may result in increased oral diseases, especially dental caries and periodontal disease, because preventive dental care is not an integral part of psychiatric care [10, 11, 14–16, 23, 27].…”
Section: Introductionmentioning
confidence: 99%
“…[13] Furthermore, a study in Virginia by Barnes et al . [14] showed that majority (38%) were diagnosed with affective mood disorder and second large proportion were diagnosed to be having schizophrenia.…”
Section: Discussionmentioning
confidence: 99%